PENGARUH CASH HOLDING, DIVIDEND PAYOUT RATIO, DAN NET PROFIT MARGIN TERHADAP INCOME SMOOTHING - Ni Putu Ayu Intan Suarnaningsih; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2020)
In terms of maintaining investor confidence to maintain investment by keeping company profits stable. Keeping the company stable is the task of company management. The purpose of this study was to determine the effect of cash holding, dividend payout ratio, and net profit margin on income smoothing. The study population includes all manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period. Population data included 152 companies, and obtained a sample of 48 company samples. The method used in this research is purposive sampling. The hypothesis is tested using logistic regression analysis. The results of logistic regression show that cash holding has no effect on income smoothing, dividend payout ratio has a positive effect on income smoothing, and net profit margin has a positive effect on income smoothing.